PENEMUAN HUKUM ( RECHTSVINDING ) OLEH HAKIM DALAM PUTUSAN PERDATA - Mardius , (Fakultas Hukum Universitas Tamansiswa Padang, 2017)
This paper reviews and discusses the discovery of law by civil judges in deciding a civil case in the Padang District Court. The source of the authors take the results of observation in the field by making observations and read filings of civil cases that were decided by the judge in deciding civil cases. To be able to decide upon a civil case the judge is not only bound to the evidence of letters and witnesses filed by the litigants but the judge also has a legal view derived from the proof, because with the verification of a judge will be able to find the law for events or legal acts or often called disputed object objects. Proof is the main requirement for the judge to find the law, so that the judge will be able to decide upon a dispute by relating a proof to another proof so as to constitute a series that raises an opinion or conclusion to the judge that it is the law. Applying the law to an event is the work of a judge to find the law in the case or case of his trial, so that the judge will be able to provide a verdict based on the evidence presented to him.